SOFSEM 2016: Theory and Practice of Computer Science

Theory and Practice of Model Transformations - 9th International Conference ICMT 2016, Held as Part of STAF 2016, Vienna, Austria, July 4-5, 2016, Proceedings

SOFSEM 2016: Theory and Practice of Computer Science - Proceedings Volume II

Automated Quality Analysis of Software Engineering Method Models - Fazal-Baqaie, Masud; Kluthe, Frank (Proceedings of the 4th International Conference on Model-Driven Engineering and Software Development)

Ganzheitliches Qualitätsmanagement in agilen Groß- Projekten - Fazal-Baqaie, Masud; Güldali, Baris; Grieger, Marvin (Proceedings of Projektmanagement und Vorgehensmodelle 2016)

Concept-Based Engineering of Situation-Specific Migration Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Engels, Gregor; Klenke, Markus (Proceedings of the 15th International Conference on Software Reuse (ICSR))

Multi-device UI Development for Task-Continuous Cross-Channel Web Applications - Yigitbas, Enes; Kern, Thomas; Urban, Patrick; Sauer, Stefan (Current Trends in Web Engineering - ICWE 2016 International Workshops, DUI, TELERISE, SoWeMine, and Liquid Web, Lugano, Switzerland, June 6-9, 2016, Revised Selected Papers)

Engineering Context-Adaptive UIs for Task-Continuous Cross-Channel Applications - Yigitbas, Enes; Sauer, Stefan (Human-Centered and Error-Resilient Systems Development - IFIP WG 13.2/13.5 Joint Working Conference 6th International Conference on Human-Centered Software Engineering, HCSE 2016, and 8th International Conference on Human Error, Safety, and System Development, HESSD 2016 Stockholm, Sweden, August 29-31, 2016, Proceedings)

Customized UI Development Through Context-Sensitive GUI Patterns - Yigitbas, Enes; Sauer, Stefan (Mensch und Computer 2016 - Workshopband, Aachen, Germany, September 4-7, 2016)

Towards a Task Driven Approach Enabling Continuous User Requirements Engineering - Fischer, Holger Gerhard; Rose, Mirko; Yigitbas, Enes; Forbrig, Peter (Joint Proceedings of REFSQ-2016 Workshops, Doctoral Symposium, Research Method Track, and Poster Track co-located with the 22nd International Conference on Requirements Engineering: Foundation for Software Quality {(REFSQ} 2016), Gothenburg, Sweden, March 14, 2016.)

Towards a Model-Driven Method for Reusing Test Cases in Software Migration Projects - Jovanovikj, Ivan; Grieger, Marvin; Yigitbas, Enes (Softwaretechnik-Trends, Proceedings of the 18th Workshop Software-Reengineering & Evolution (WSRE) & 7th Workshop Design for Future (DFF))

Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing)
Integrating apps on mobile devices into applications running on other devices is usually difficult. For instance, using a messenger on a smartphone to share a text written on a desktop computer often ends up in a cumbersome solution to transfer the text, because many applications are not designed for such scenarios. In this paper, we present an approach enabling the integration of apps running on Android devices into applications running on other devices and even other platforms. This is achieved by specifying adapters for Android apps, which map their services to a platform-independent service interface. For this purpose, we have developed a domain-specific language to ease the specification of such mappings. Our approach is applicable without the need to modify the existing Android apps providing the service. We analyzed its feasibility by implementing our approach and by specifying mappings for several popular Android apps, e.g., phone book, camera, and file explorer.
Keywords: Cross-Device; Integration; Android; Adapter; DSL

UUX Method Selection - Fischer, Holger Gerhard; Kauer-Franz, Michaela; Winter, Dominique; Latt, Stefan (i-com)

Human-Centered Software Engineering as a Chance to Ensure Software Quality Within the Digitization of Human Workflows - Fischer, Holger Gerhard; Senft, Björn (Human-Centered and Error-Resilient Systems Development)

Towards a Task Driven Approach Enabling Continuous User Requirements Engineering - Fischer, Holger Gerhard; Rose, Mirko; Yigitbas, Enes (Joint Proceedings of the REFSQ 2016 Co-Located Events. 2nd Workshop on Continuous Requirements Engineering (CRE))

Mensch und Computer 2016 - Usability Professionals. Tagungsband

Thoughts on the Evolution Towards Model-Integrating Software - Derakhshanmanesh, Mahdi; Grieger, Marvin; Ebert, Jürgen; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 3rd Workshop Model-Based and Model-Driven Software Modernization (MMSM))

A Method Base for the Situation-Specific Development of Model-Driven Transformation Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 3rd Workshop Model-Based and Model-Driven Software Modernization (MMSM))

Formate als Sackgassen: Handlungsempfehlungen - Bohl, Benjamin W.; Berndt, Axel; Senft, Björn (Konferenzabstracts der 3. Tagung des Verbands "Digital Humanities im deutschsprachigen Raum e. V.")

Design Thinking als Methode in den Digital Humanities. Optionen interdisziplinären, forschenden Lehrens und Lernens - Greulich, Markus; Karthaus, Nicola; Oberthür, Simon; Schmidt, Ariane; Senft, Björn; Stog, Kristina (Konferenzabstracts der 45. Jahrestagung der Deutschen Gesellschaft für Hochschuldidaktik)